PENGARUH KONSTRUK RELASIONAL PADA CUSTOMER REFERRAL DAN JUMLAH JASA YANG DIBELI DENGAN UMUR RELASIONAL SEBAGAI VARIABEL PEMODERASI - Retnawati, Berta Bekti; Purwanto, BM. (Journal of Indonesian Economy and Business, 2004)
This research aims to examine the effect of relational constructs (trust, affectivecommitment, calculative commitment, satisfaction, and payment equity) on customerreferral and number of service purchased with age of relationship as moderating variable.The data were collected with convenience sample from 181 (response rate 90,5%)customers of insurance companies in Special Province of Yogyakarta. In line with thecharacteristics of customers of the company, the individuals in the sample could bedescribed as productive age, rather prosperous and well educated. The averagerelationship age of the respondents was approximately 4,49 years, while the averagenumber of services purchased was approximately 1,49.All hypotheses were tested with hierarchical regression analysis (HRA). The results onthe antecedents of customer referrals are in line with prior research, as author find thattrust, affective commitment, satisfaction, and payment equity are positively related tocustomer referrals. We found significant relationship only the relational construct ofaffective commitment and the number services purchased.No moderating effect of relationship age is found in the customer referral model. Withrespect to the number of services purchased, a moderating effect of relationship age on the effect of affective commitment is found. There is argument about the discrepancy between the customer referral model and the number of services purchased model with regard to the moderating effect of relationship age. This increasing confidence is indeed important it concerns decisions that have important consequences, such as the purchase of new insurance policies. However, it might be less important when behavior has fever direct consequences for the customer, such as customer referral.Keywords: relational constructs, customer referral, number of service purchased, andrelational age